ROLE AND IMPORTANCE OF PRACTICING PSYCHOLOGIST IN SCHOOLS (International conference on multidisciplinary science, 2023)
This article describes the activities of a practicing psychologist in schools and his role in the organization of psychological services and the creation of a social environment in schools.